Development of a TEG-based household griller prototype using charcoal and charcoal briquettes as the hot source and a reusable ice pack as the cold source with charging capability - Berjolano, Vincent Paul D.V.; Chua, Claude Vanne T.; Llantino, Ivan L; Vergara, Dexter Q. 4 0 16; 5 (2023)
u
Undergraduate Thesis: (Bachelor of Science in Electrical Engineering) - Pamantasan ng Lungsod ng Maynila, 2023.
Keywords: 2 -- 0; 6; 20; 20; 2